2018
DOI: 10.1016/j.physe.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Stability of direct band gap under mechanical strains for monolayer MoS2, MoSe2, WS2 and WSe2

Abstract: Single layer transition-metal dichalcogenides materials (MoS 2 , MoSe 2 , WS 2 and WSe 2) are investigated using the first-principles method with the emphasis on their responses to mechanical strains. All these materials display the direct band gap under a certain range of strains from compressive to tensile (stable range). We have found that this stable range is different for these materials. Through studying on their mechanical properties again using the first-principles approach, it is unveiled that this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 40 publications
4
51
0
Order By: Relevance
“…These excellent properties have resulted in many applications, such as phototransistor [6,7], flexible optoelectronics [8], self-powered nanosystems [9,10] and smart MEMS/NEMS [8,11,12]. During the last decade, several TMDs have been extensively investigated, both in theory and experiment [2,[13][14][15][16][17].…”
Section: Hementioning
confidence: 99%
See 2 more Smart Citations
“…These excellent properties have resulted in many applications, such as phototransistor [6,7], flexible optoelectronics [8], self-powered nanosystems [9,10] and smart MEMS/NEMS [8,11,12]. During the last decade, several TMDs have been extensively investigated, both in theory and experiment [2,[13][14][15][16][17].…”
Section: Hementioning
confidence: 99%
“…Furthermore, some important properties distinguished from the traditional two-dimensional (2D) TMDs have been reported , such as excellent linear electronic and optical tunability [2]. Many previous studies have shown that one can tune the electronic and optical properties of the TMDs by applying mechanical strains [2,16,17,[20][21][22]. Although the optical properties of the monolayer PdS2, electron transport properties and stability of the bilayer and bulk PdS2 have been studied in references [2,23,24], there are very few studies on the first principles analysis of the orthorhombic PdS2.…”
Section: Hementioning
confidence: 99%
See 1 more Smart Citation
“…Among these, MoS2 is not suitable for tunnel FET applications due to its large band gap of 1.8 eV, which significantly reduces the band-to-band tunneling probability. Semiconducting MoTe2 (2H-phase) suffers from the stability issue [15], [20]. Therefore, this is not feasible for reliable FET realization, especially under external strain.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, traditional transitionmetal dichalcogenide (TMD) semiconductors have become very promising candidates among the 2D materials series owing to the direct band gap behavior in monolayer TMDs at the K point, 2 along with excellent electronic, catalytic, optical, and mechanical properties. [3][4][5][6][7][8][9][10][11][12] Furthermore, TMD materials exhibit superior photoluminescence behavior, 3,4 piezoelectric properties, 13,14 and controllable optical performance by modulating valleys in the k space. [15][16][17][18] The development of several optoelectronic devices, such as strain sensors, 19 transistors, 20 and highly sensitive and broadband photodetectors [21][22][23] will highly benet from the assistance of these inherent properties.…”
Section: Introductionmentioning
confidence: 99%